MINERAL SOLUBILITIES IN THE NA-K-MG-CA-CL-SO4-H2O SYSTEM: A RE-EVALUATION OF THE SULFATE CHEMISTRY IN THE SPENCER-MOLLER-WEARE MODEL - A CHEMICAL EQUILBRIUM MODEL FOR THE NA-K-CA-MG-CL-SO4-H2O SYSTEM AT TEMPERATURES BELOW 25°C - Marion G.M.; Farren R.E. (My University, 1999)
The Spencer-Moller-Weare (SMW) (1990) model is parameterized for the Na-K-Mg-Ca-Cl-SO4-H2O system over the temperature range from -60° to 25°C. This model is one of the few complex chemical equilibrium models for aqueous solutions parameterized for subzero temperatures. The primary focus of the SMW model parameterization and validation deals with chloride systems. There are problems with the sulfate parameterization of the SMW model, most notably with sodium sulfate and magnesium sulfate. The primary objective of this article is to re-estimate the Pitzer-equation parameters governing interactions among sodium, potassium, magnesium, and calcium with sulfate in the SMW model.A mathematical algorithm is developed to estimate 22 temperature-dependent Pitzer-equation parameters. The sodium sulfate reparameterization reduces the overall standard error (SE) from 0.393 with the SMW Pitzer-equation parameters to 0.155. Similarly, the magnesium sulfate reparameterization reduces the SE from 0.335 to 0.124. In addition to the sulfate reparameterization, five additional sulfate minerals are included in the model, which allows a more complete treatment of sulfate chemistry in the Na-K-Mg-Ca-Cl-SO4-H2O system.Application of the model to seawater evaporation predicts gypsum precipitation at a seawater concentration factor (SCF) of 3.37 and halite precipitation at an SCF of 10.56, which are in good agreement with previous experimental and theoretical estimates. Application of the model to seawater freezing helps explain the two pathways for seawater freezing. Along the thermodynamically stable ''Gitterman pathway,'' calcium precipitates as gypsum and the seawater eutectic is -36.2°C. Along the metastable ''Ringer-Nelson-Thompson pathway,'' calcium precipitates as antarcticite and the seawater eutectic is -53.8°C.